Benefits and Challenges Associated with the Implementation of Lean in Transportation Agencies. Issue 2 (February 2022) - Parajuli, Manish; Harper, Christofer M.; Senior, Bolivar; Grigg, Neil
The highway construction industry constantly looks to increase productivity while public transportation agencies face challenges of shrinking budgets and staff numbers, even as the work continues to increase in size and demand. As a paradigm to maximize value and minimize waste with the resources available, Lean offers promise to enhance productivity, quality, and service. This study investigates the implementation of Lean by evaluating Lean conditions, practices, benefits, and challenges as expressed by U.S. and UK public transportation highway agencies as well as comparing the implementation of Lean between these agencies. Using a comprehensive literature review and formal interviews with six state departments of transportation along with Highways England from the UK, the findings show that Lean is intended to make process improvements to boost products and services to consumers. By creating a culture of continuous improvement, transportation agencies can improve their processes and increase their efficiencies and performance. Conversely, transportation agencies struggle to educate their employees and stakeholders in their understanding and practices of Lean, which causes confusion and ineffectiveness. Comparing the U.S. and UK transportation agencies, the approach to Lean implementation differs from a top-down approach for U.S. agencies to a bottom-up approach for Highways England. Furthermore, Highways England has an established tool for measuring Lean while development of quantifiable Lean measures is in its infancy in U.S. agencies. Overall, while the sample is limited, this exploratory study provides information for transportation agencies to use in consideration of implementing Lean.